Strategi Branding dalam Promosi Penjualan Produk Pertanian Olahan PT. Hatten Bali untuk Pasar Pariwisata Indonesia - Diarta, I Ketut Surya; Lestari, Putu Widhianti; Dewi, Ida Ayu Putu Citra (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2016)
Branding becomes inevitable in sales promotion strategy of products and services in the era of globalization. However, the difficult challenge of agricultural products branding related to standardization because it involves a biological process that can not be fully controlled. Moreover, if the intended target market is specific to the tourism market.This paper discusses branding strategy used by agribusiness company PT. Hatten Bali in promoting wine processed "Hatten Wines" for the tourism market in Indonesia. Data were collected through in-depth interviews and observations technique and were analyzed by descriptive qualitative method. PT. Hatten Bali uses three strategies of branding ot its wines pruducts, namely: (1) producer branding (Hatten Wines Aga White, Hatten Wines Aga Red, Hatten Wines Alexandria, Hatten Wines Rose, Hatten Wines Sparkling Tunjung, and Hatten Wines Sparkling Jepun), (2) retail branding (Dragonfly Moscato and Two Island), and (3) geographical branding (Pino de Bali and Dewi Sri). All three branding strategies have differences in agricultural raw material processed, the target market, and typology of use in order to meet the company's sales target. Branding strategy proved to be applicable and effective used in processed agricultural products sales promotion strategies just like used in manufacturing products and other services. Agribusiness entrepreneurs should consider the use of branding in sales promotion to better compete with competitors.
Keywords: Branding, Promotion, Agriculture, Wines, Tourism